Phytochemical Analysis, Antinociceptive and Anti-inflammatory Activities of Mimusops elengi Bojer Leaf Extract-loaded Chitosan Nanoparticles in Albino Mice - Ukwubile, Cletus Anes; Clement, Chidi Kaosi (Sciences of Phytochemistry, 2026)
The present study evaluated the antinociceptive and anti-inflammatory activities of Mimusops elengi Bojer leaf extract encapsulated in chitosan nanoparticles (CS-NPs) using murine models, to determine whether nanoparticle formulation enhances the biological effects of a methanolic plant extract. Preliminary phytochemical screening was conducted using established qualitative colorimetric assays, which indicated the presence of major secondary metabolite classes, including phenolics and flavonoids; these tests were intended for compositional inference rather than definitive compound identification. Total phenolic and flavonoid contents were subsequently quantified using spectrophotometric methods, yielding 806.12 mg gallic acid equivalents (GAE)/g and 103.08 mg quercetin equivalents (QE)/g of extract, respectively. Antinociceptive activity was assessed using acetic acid–induced writhing and hot-plate assays, while anti-inflammatory effects were evaluated via the carrageenan-induced paw edema model. Animals treated with M. elengi–loaded CS-NPs exhibited statistically significant reductions in writhing responses, prolonged pain reaction latency, and decreased paw edema when compared with untreated controls and animals receiving the crude extract (p < 0.05). Inflammatory mediator analysis further demonstrated significant downregulation of pro-inflammatory cytokines (TNF-α, IL-1β, and PGE₂) alongside upregulation of anti-inflammatory cytokines (IL-10 and IL-22). Oxidative stress assessment showed reduced malondialdehyde (MDA) levels, indicating attenuation of lipid peroxidation. All experiments were conducted with appropriate replication, and data were subjected to statistical analysis to ensure reproducibility. While the phytochemical screening provides preliminary compositional insights, the observed pharmacological effects are attributed to the combined action of extract constituents and improved delivery via chitosan nanoparticles. Overall, the findings support the hypothesis that nanoparticle-based formulation can enhance the antinociceptive and anti-inflammatory efficacy of M. elengi leaf extract, highlighting its potential as a complementary therapeutic approach while underscoring the need for further compound-level characterization and safety evaluation.